دراسة مقارنة بين طريقة الامتزاز على العمود الكرماتوغرافي (الاستشراب) وطريقة الرحلان الكهربائي على غراء الأغاروز لتعيين قيمة الخضاب A2 (HbA2) - عابدين, بسام; جرجس, ميخائيل; بدر, حصه (Latakia University Journal -Medical Sciences Series, 2019)
تمت الدراسة على 73 حالة من فئات عمرية مختلفة ودون تحديد للجنس في مشفى الأسد الجامعي باللاذقية بين عامي 2002-2003 منها 26 حالة β تلاسيميا صغرى . أجري لجميع العينات رحلان كهربائي على غراء الأغاروز بتيار شدته 100-120AM وPH=8.6, وكذلك استشراب على العمود لتعيين قيمة HbA2, باستخدام طاقم عمل جاهز من شركة Biosystem®. خلاصة النتائج: 1- بالنسبة للحالات الطبيعية: كان متوسط قيم A2 بطريقة الرحلان الكهربائي يساوي 3.172%, والانحراف المعياري لها 0.369, وبذلك يكون مجال الثقة لهذا المتوسط: كان متوسط قيم A2 بطريقة الاستشراب على العمود 3.248%, والانحراف المعياري لها 0.598, وبذلك يكون مجال الثقة لهذا المتوسط: 2- بالنسبة لحالات التلاسيميا بيتا الصغرى : كان متوسط قيم A2 بطريقة الرحلان الكهربائي 5.531%, والانحراف المعياري لها 0.779, وبذلك يكون مجال الثقة لهذا المتوسط: كان متوسط قيم A2 بطريقة الاستشراب على العمود 5.354%, والانحراف المعياري لها 0.796, وبذلك يكون مجال الثقة لهذا المتوسط: 3- لم نجد أي فرق جوهري بين طريقتي القياس ، الرحلان الكهربائي والاستشراب على العمود الكروماتوغرافي عند دراسة كلا المجموعتين السابقتين . This study was carried out on 73 states of different age groups, without identifying the sex, in Al-Assad Hospital in Lattakia between 2002–2003. 26 of these were β- thalassemia trait. All these samples were subjected to electrophoresis on gel agarose with an electric current whose intensity was 100- 120 Am, and Ph = 8.6. and a microculomn chromatography to identify the value of HbA2, by using prepared stuff from Biosystem® Company. Summary of results: 1- Regarding normal cases : -The average values of A2 in the way of electrophoresis was 3.172%, its standard deviation was 0.369, so the confidence rang for this average is: P[3.067 ≤ X ≤ 3.278]= 0.95 -The average values of A2 in of microcolumn chromatography was 3.248%, its standard deviation was 0.598, so the confidence rang for this average is: P[3.077 ≤ X ≤ 3.419]= 0.95 2- Regarding β- thalassemia trait cases: -The average values of A2 in the way of electrophoresis was 5.531%, its standard deviation was 0.779, so the confidence rang for this average is: P[5.22 ≤ X ≤ 5.84]= 0.95 -The average values of A2 in microcolumn chromatography was 5.354%, its standard deviation was 0.796, so the confidence rang for this average is: P[5.03≤ X ≤ 5.67]= 0.95 3-We find no significant difference between the two ways of measurement electrophoresis and microcolumn chromatography in the study of the two groups.